Glass ceramic, preparation method thereof and glass product
By optimizing the chemical composition of the crystal-crystalline glass, the problem of high thermal expansion coefficient of traditional crystal-crystalline glass is solved, and microcrystalline glass suitable for high temperature scenarios is prepared, with the advantages of low expansion, heat resistance, and high mechanical strength.
Patent Information
- Application Number
- CN202411706051.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The thermal expansion coefficient of traditional microcrystalline glass is relatively high, which limits its application in high temperature scenarios.
By rationally designing the chemical composition of microcrystalline glass, including components such as SiO2, Al2O3, Li2O, Na2O, MgO, ZnO, CaO, BaO, TiO2, ZrO2, P2O5 and La2O3, its thermal expansion coefficient and mechanical properties are optimized.
Microcrystalline glass with low thermal expansion coefficient, excellent mechanical properties and high visible light transmittance are prepared, which is suitable for high temperature scenarios.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass technology, and in particular to a microcrystalline glass and a preparation method thereof, and a glass product. Background Art
[0002] Glass-ceramics is a new type of building decoration material, the main component of which is silicate. Due to its good chemical stability and mechanical strength, it is widely used in construction, home appliances, automobiles and other fields.
[0003] The main preparation method of glass-ceramics is to precipitate a large number of tiny crystals inside the glass through high-temperature melting, molding, heat treatment and other steps, thereby improving the strength and hardness of the glass. However, the thermal expansion coefficient of traditional glass-ceramics is relatively high, and it is easy to deform in high-temperature environments, which limits its application in high-temperature scenarios.
[0004] Therefore, further improvement of traditional glass-ceramics is still needed. Summary of the invention
[0005] Based on this, one or more embodiments of the present application provide a microcrystalline glass with a low thermal expansion coefficient and excellent mechanical properties, a preparation method thereof, and a glass product.
[0006] According to a first aspect of an embodiment of the present application, a glass-ceramic is provided, comprising the following components by mass percentage:
[0007] SiO2 54%~68%, Al2O3 15%~24.8%, Li2O 0.5%~4.5%, Na2O 0~1%, MgO 1%~5%, ZnO 1%~5%, CaO 0~1%, BaO 0~3%, TiO2 0.5%~4%, ZrO2 1%~5%, P2O5 0.5%~3% and La2O3 0.1%~1%.
[0008] In some of the embodiments, the sum of the mass percentages of TiO2, ZrO2 and P2O5 is a%, and satisfies 5.57≤a≤8.73.
[0009] In some of the embodiments, the mass percentage of TiO2 is x%, the sum of the mass percentages of ZrO2 and P2O5 is y%, and 0.1≤x / y≤0.97 is satisfied.
[0010] In some of the embodiments, the sum of the mass percentages of SiO2, Al2O3, Li2O and La2O3 is m%, the sum of the mass percentages of TiO2, ZrO2 and P2O5 is n%, and 9.39≤m / n≤15.42 is satisfied.
[0011] In some of the embodiments, the sum of the mass percentages of MgO, ZnO, CaO and BaO is q%, the sum of the mass percentages of Na2O and Li2O is p%, and 1.52≤q / p≤5.69 is satisfied.
[0012] In some of the embodiments, the sum of the mass percentages of MgO and ZnO is b%, the mass percentage of Al2O3 is c%, and 0.21≤b / c≤0.42 is satisfied.
[0013] In some embodiments, the glass-ceramics satisfies at least one of the following conditions:
[0014] (1) The glass-ceramics comprises the following components, measured by mass percentage: SiO2 56%-68%, Al2O3 15.5%-24.8%, Li2O 1.5%-4%, Na2O 0.5-1%, MgO 1.5%-3.5%, ZnO 1.5%-5%, CaO 0.3%-0.9%, BaO 0-3%, TiO2 1%-4%, ZrO2 1%-4%, P2O5 0.5%-2.4% and La2O3 0.1%-0.9%;
[0015] (2) The main crystalline phase of the glass-ceramics includes one or more of quartz solid solution, spodumene and spinel;
[0016] (3) The crystallinity of the glass-ceramics is 45% to 58%.
[0017] According to a second aspect of the embodiments of the present application, a method for preparing glass-ceramics is provided, comprising the following steps:
[0018] Providing raw materials according to the above-mentioned components of the glass-ceramics, and mixing the raw materials to prepare a mixture;
[0019] The mixture is subjected to melting treatment, molding treatment, annealing treatment and crystallization treatment to obtain the microcrystalline glass.
[0020] In some embodiments, the preparation method satisfies at least one of the following conditions:
[0021] (1) The melting treatment temperature is 1620°C to 1660°C and the time is 4h to 8h;
[0022] (2) The temperature of the molding process is 1280°C to 1380°C;
[0023] (3) The annealing treatment is performed at a temperature of 550°C to 650°C and for a time of 4h to 6h;
[0024] (4) The crystallization treatment is performed at a temperature of 750°C to 900°C and for a time of 1.5h to 6h;
[0025] (5) The crystallization step includes: heating to a crystallization temperature at a rate of 2°C / min to 5°C / min;
[0026] (6) After the crystallization treatment, the following steps are included: cooling to room temperature at a rate of 0.5°C / min to 2°C / min.
[0027] According to a third aspect of an embodiment of the present application, a glass product is provided, comprising the above-mentioned glass-ceramics or glass-ceramics prepared by the above-mentioned method for preparing glass-ceramics.
[0028] Compared with the traditional technology, this application has the following beneficial effects:
[0029] The chemical composition of microcrystalline glass is reasonably designed in the present application. SiO2 and Al2O3 are the main components of the glass network structure, Li2O can reduce the high-temperature viscosity of the glass, Na2O can improve the melting performance of the glass, MgO has a fluxing effect, ZnO can reduce the high-temperature viscosity, CaO and BaO can reduce the melting temperature of the glass, TiO2 and La2O3 can promote the crystallization of the glass, ZrO2 can improve the crystallization efficiency of the glass, and P2O5 can increase the solubility of the glass components; the above-mentioned components cooperate with each other and work synergistically under the specific ratio of the present application, so as to prepare microcrystalline glass with low thermal expansion coefficient, excellent mechanical properties and high visible light transmittance. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0032] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0033] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0034] The temperature parameters in this application, unless otherwise specified, allow both constant temperature treatment and temperature fluctuation within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0035] Some embodiments of the present application provide a glass-ceramic, comprising the following components by mass percentage:
[0036] SiO254%~68%, Al2O315%~24.8%, Li2O 0.5%~4.5%, Na2O 0~1%, MgO 1%~5%, ZnO 1%~5%, CaO 0~1%, BaO 0~3%, TiO20.5%~4%, ZrO21%~5%, P2O50.5%~3% and La2O30.1%~1%.
[0037] SiO2 is the main body of the glass network skeleton and is also the largest component in the glass composition. In this application, the mass percentage of SiO2 is 54% to 68%. Within this composition range, the thermal expansion coefficient of microcrystalline glass is low, and the glass hardness and high-temperature viscosity are moderate.
[0038] In the present application, the mass percentage of SiO2 is "54% to 68%", which means the minimum and maximum values in the range of 54% to 68%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67% or 68%; or a range consisting of any two of these values, such as: 56.5% to 62.5%.
[0039] In some optional examples, the mass percentage of SiO2 is 56%~68%.
[0040] Al2O3 is a necessary component for forming a glass network structure. After heat treatment, most of it is a component of the β-quartz solid solution crystal phase, and a small amount exists in the residual glass phase. By controlling the mass percentage of Al2O3 within a specific range, microcrystalline glass with a low thermal expansion coefficient and high transparency can be prepared, while making the viscosity of the microcrystalline glass moderate.
[0041] In the present application, the mass percentage of Al2O3 is "15% to 24.8%", which means the minimum and maximum values in the range of 15% to 24.8%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 24.8%; or a range consisting of any two of these values, such as: 16.5% to 20.5%.
[0042] In some optional examples, the mass percentage of Al2O3 is 15%~22%.
[0043] Li2O can reduce the high-temperature viscosity of glass and is also an essential component for the formation of β-quartz solid solution. Controlling its content within a specific range can make the crystallization ability of microcrystalline glass moderate and the crystallization process less likely to get out of control.
[0044] In the present application, the mass percentage of Li2O is "0.5% to 4.5%, which means the minimum and maximum values in the range of 0.5% to 4.5%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%; or a range consisting of any two of these values, such as: 2.2% to 4.2%.
[0045] In some optional examples, the mass percentage of Li2O is 1.5%~4%.
[0046] The addition of Na2O can improve the melting performance of glass-ceramics, but it will increase the proportion of residual glass phase in the glass-ceramics, increase the thermal expansion coefficient, and may cause the product to become hazy; therefore, its mass percentage needs to be controlled within a specific range to achieve the purpose of improving the glass melting performance.
[0047] In the present application, the mass percentage of Na2O is "0-1%, which means the minimum and maximum values in the range of 0-1%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; or a range consisting of any two of these values, such as: 0.4%-0.8%.
[0048] In some optional examples, the mass percentage of Na2O is 0.5%~1%.
[0049] MgO has a certain fluxing effect under high temperature conditions, and can also reduce the crystallization tendency and crystallization rate, thereby improving the chemical stability and mechanical strength of the glass.
[0050] The mass percentage of MgO in this application is "1% to 5%", which means the minimum and maximum values in the range of 1% to 5%, and any value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%; or a range consisting of any two of these values, such as: 0.4% to 4.4%.
[0051] In some optional examples, the mass percentage of MgO is 1.5% to 3.5%.
[0052] ZnO has the effect of reducing high temperature viscosity and increasing low temperature viscosity. At the same time, ZnO can reduce the CTE of glass and improve chemical stability and thermal stability. The mass percentage of ZnO in this application should not be too high. As the amount of ZnO added increases, the structure becomes looser and the crystallization activation energy is reduced, making it easier for β-quartz to transform into β-spodumene, and coarsening the crystals, so that the sample becomes white and opaque.
[0053] In the present application, the mass percentage of ZnO is "1% to 5%", which means the minimum and maximum values in the range of 1% to 5%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%; or a range consisting of any two of these values, such as: 0.4% to 4.4%.
[0054] In some optional examples, the mass percentage of ZnO is 1.5% to 5%.
[0055] CaO can reduce the melting temperature of glass-ceramics. During the heat treatment process, the crystallization rate of glass decreases with the increase of CaO addition, while the softening temperature, crystallization temperature and thermal expansion coefficient of glass increase with the increase of CaO addition. Therefore, the mass percentage of CaO needs to be reasonably regulated.
[0056] In the present application, the mass percentage of CaO is "0-1%", which means the minimum and maximum values in the range of 0-1%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; or a range consisting of any two of these values, such as: 0.3%-0.8%.
[0057] In some optional examples, the mass percentage of CaO is 0.3%~0.9%.
[0058] BaO can not only lower the melting temperature of glass, but also improve the transparency of glass; however, too high BaO content may cause corrosion to refractory materials.
[0059] In the present application, the mass percentage of BaO is "0-3%", which means the minimum and maximum values in the range of 0-3%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5% or 3%; or a range consisting of any two of these values, such as: 0.5%-2.8%.
[0060] In some optional examples, the mass percentage of BaO is 0% to 2.8%.
[0061] TiO2 can not only promote the crystallization of microcrystalline glass and improve the crystallization ability of glass, but also reduce the viscosity of the glass system at high temperature and improve the melting and processing performance of glass.
[0062] In the present application, the mass percentage of TiO2 is "0.5% to 4%", which means the minimum and maximum values in the range of 0.5% to 4%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%; or a range consisting of any two of these values, such as: 0.5% to 3.6%.
[0063] In some optional examples, the mass percentage of TiO2 is 1%~4%.
[0064] ZrO2 can make the microcrystalline glass have better crystallization efficiency, and at the same time increase the stable temperature range of β-quartz solid solution, which is beneficial to the formation of β-quartz solid solution and can prevent the transformation of β-quartz solid solution to β-spodumene solid solution; at the same time, ZrO2 can make the grain distribution in the microcrystalline glass sample more dispersed, thereby avoiding the aggregation of grains leading to increased local stress and easy cracking; in addition, independently dispersed grains are easier to fill in the defects of the glass, making the structure of the microcrystalline glass denser and improving the flexural strength.
[0065] In the present application, the mass percentage of ZrO2 is "1% to 5%", which means the minimum and maximum values in the range of 1% to 5%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%; or a range consisting of any two of these values, such as: 0.8% to 4.2%.
[0066] In some optional examples, the mass percentage of ZrO2 is 1%~4%.
[0067] The addition of P2O5 can significantly increase the solubility of ZrO2 and avoid the formation of ZrO2 stones in the matrix glass. In addition, P2O5 can form AlPO4 with Al2O3 to replace SiO2, reduce the high-temperature viscosity of the matrix glass, improve the uniformity and forming properties of the glass, reduce the transformation trend of β-quartz solid solution to β-spodumene solid solution, and adjust the CTE of microcrystalline glass.
[0068] In the present application, the mass percentage of P2O5 is "0.5% to 3%", which means the minimum and maximum values in the range of 0.5% to 3%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5% or 3%; or a range consisting of any two of these values, such as: 0.8% to 2.6%.
[0069] In some optional examples, the mass percentage of P2O5 is 0.5%~2.4%.
[0070] After adding La2O3, the microcrystalline glass can cut off ultraviolet light and reduce the viscosity of the glass liquid; it can also promote crystallization and weaken the transformation of the metastable β-quartz solid solution to the stable phase β-spodumene solid solution.
[0071] In the present application, the mass percentage of La2O3 is "0.1% to 1%", which means the minimum and maximum values in the range of 0.1% to 1%, and every value between the minimum and maximum values. Specifically, it includes but is not limited to the point values in the embodiment and the following point values: 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; or a range consisting of any two of these values, such as: 0.25% to 0.75%.
[0072] In some optional examples, the mass percentage of La2O3 is 0.1%~0.9%.
[0073] In some embodiments, the sum of the mass percentages of TiO2, ZrO2, and P2O5 is a%, and satisfies 5.57≤a≤8.73.
[0074] As an example, the value of a can be but is not limited to 5.57, 5.6, 5.7, 5.8, 5.9, 6, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7 or 8.73.
[0075] In some of the embodiments, the mass percentage of TiO2 is x%, the sum of the mass percentages of ZrO2 and P2O5 is y%, and 0.1≤x / y≤0.97 is satisfied.
[0076] As an example, the value of x / y may be, but is not limited to, specific values such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.97.
[0077] It can be understood that selecting TiO2, ZrO2 and P2O5 as composite nucleating agents can make the crystal grains of the microcrystalline glass finer, with higher peel strength and better transparency after crystallization.
[0078] In some embodiments, the sum of the mass percentages of SiO2, Al2O3, Li2O and La2O3 is m%, the sum of the mass percentages of TiO2, ZrO2 and P2O5 is n%, and 9.39≤m / n≤15.42 is satisfied.
[0079] As an example, the value of m / n may be, but is not limited to, 9.39, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15 or 15.42.
[0080] It can be understood that controlling the value of m / n within the above-mentioned specific range can cause the microcrystalline glass to precipitate a crystalline phase mainly composed of β-quartz solid solution, and have the effects of low expansion and heat resistance.
[0081] In some of the embodiments, the sum of the mass percentages of MgO, ZnO, CaO and BaO is q%, the sum of the mass percentages of Na2O and Li2O is p%, and 1.52≤q / p≤5.69 is satisfied.
[0082] As an example, the value of q / p may be, but is not limited to, specific values such as 1.52, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5 or 5.69.
[0083] Understandably, R2O and RO can form a "mixed alkali-alkaline earth effect", thereby significantly increasing the expansion softening temperature of the glass; therefore, controlling the value of q / p within the above-mentioned specific range can achieve better results.
[0084] In some of the embodiments, the sum of the mass percentages of MgO and ZnO is b%, the mass percentage of Al2O3 is c%, and 0.21≤b / c≤0.42 is satisfied.
[0085] As an example, the value of b / c can be but is not limited to 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41 or 0.42.
[0086] Understandably, adding MgO and ZnO can reduce the cost of raw materials and lower the liquidus temperature, but excessive content will cause the precipitation of crystalline phases with higher CTE, such as cordierite and spinel, during the crystallization of the glass, affecting the performance of the product.
[0087] In some optional examples, the microcrystalline glass includes the following components by mass percentage:
[0088] SiO256%~68%, Al2O315.5%~24.8%, Li2O 5%~4%, Na2O 0.5~1%, MgO 5%~3.5%, ZnO5%~5%, CaO 0.3%~0.9%, BaO 0~3%, TiO21%~4%, ZrO21%~4%, P2O50.5%~3% and La2O30.1%~0.9%.
[0089] In some embodiments, the main crystalline phase of the glass-ceramics includes one or more of quartz solid solution, spodumene and spinel.
[0090] In some of the embodiments, the crystallinity of the glass-ceramics is 45% to 58%.
[0091] The microcrystalline glass of the present application is not easily deformed under high temperature conditions, which improves its application value in high temperature scenarios; and the microcrystalline glass of the present application does not require the use of a large amount of scarce resources such as lithium, and has a low preparation cost.
[0092] The softening temperature of the above-mentioned glass-ceramics is above 900°C, and the expansion coefficient is -2.6×10 -7 / ℃~5×10 -7 / ℃, impact strength reaches 0.72J, and transmittance is over 86%; it has the advantages of good heat resistance, low expansion coefficient, high mechanical strength and transparent appearance, and can be used in high-temperature scenes such as electromagnetic heating panels and home panels.
[0093] The components of the microcrystalline glass of the present application do not contain toxic and harmful raw materials such as As2O3 and Sb2O3, thereby reducing pollution to the environment.
[0094] Some embodiments of the present application also provide a method for preparing glass-ceramics, including S10 and S20.
[0095] S10: providing raw materials according to the above-mentioned components of the microcrystalline glass, mixing the raw materials, and preparing a mixture.
[0096] S20: subjecting the mixture to melting, molding, annealing and crystallization to obtain glass-ceramics.
[0097] In some embodiments, the temperature of the melting treatment in S20 is 1620°C to 1660°C, and the time is 4h to 8h. As an example, the temperature of the melting treatment may be, but not limited to, specific values such as 1620°C, 1625°C, 1630°C, 1635°C, 1640°C, 1645°C, 1650°C, 1655°C or 1660°C; the time of the melting treatment may be, but not limited to, specific values such as 4h, 5h, 6h, 7h or 8h.
[0098] The present application can effectively reduce the melting temperature of the microcrystalline glass by optimizing and rationally designing its components, thereby reducing the production difficulty and saving production costs.
[0099] In some embodiments, the temperature of the molding process in S20 is 1280° C. to 1380° C. As an example, the temperature of the molding process may be, but is not limited to, specific values such as 1280° C., 1290° C., 1300° C., 1310° C., 1320° C., 1330° C., 1340° C., 1350° C., 1360° C., 1370° C. or 1380° C.
[0100] In some embodiments, the temperature of the annealing treatment in S20 is 550°C to 650°C, and the time is 4h to 6h. As an example, the temperature of the annealing treatment may be, but not limited to, specific values such as 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C; the time of the annealing treatment may be, but not limited to, specific values such as 4h, 4.5h, 5h, 5.5h or 6h.
[0101] In some embodiments, the temperature of the crystallization treatment in S20 is 750°C to 900°C, and the time is 1.5h to 6h. As an example, the temperature of the crystallization treatment may be, but is not limited to, specific values such as 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C or 900°C. The time of the crystallization treatment may be, but is not limited to, specific values such as 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h.
[0102] In some embodiments, the crystallization treatment step includes: heating from room temperature to the expansion softening temperature at a rate of 7°C / min~10°C / min; then heating to the crystallization temperature at a rate of 2°C / min~5°C / min; after crystallization is completed, cooling to room temperature at a rate of 0.5°C / min~2°C / min.
[0103] The present application optimizes the temperature, time, and heating and cooling rates of the crystallization process so that the microcrystalline glass forms a specific crystal structure during the crystallization process, thereby obtaining microcrystalline glass with heat resistance, low expansion, high strength and transparency.
[0104] Some embodiments of the present application also provide a glass product, including the above-mentioned microcrystalline glass or microcrystalline glass produced by the above-mentioned method for preparing microcrystalline glass.
[0105] Glass products containing the above-mentioned microcrystalline glass can be applied to technical fields such as household appliances, architectural decoration and automobile manufacturing.
[0106] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0107] Example 1
[0108] (1) Providing raw materials: Select ultra-white sand, aluminum oxide powder, lithium carbonate, sodium carbonate, magnesium oxide, zinc oxide, calcium oxide, barium oxide, titanium dioxide, zirconium oxide, ammonium dihydrogen phosphate, and lanthanum oxide as raw materials, weigh the raw materials according to the required component ratio, put them into a mixer for mixing, and prepare a uniform mixture; the mixing time is 30 minutes and the mixing speed is 500 rpm. The glass component ratio in Example 1 is shown in Table 1.
[0109] (2) Preparing basic glass: pouring the mixture obtained in step (1) into a platinum crucible, placing it in a high-temperature furnace, heating it to 1630°C in an inert atmosphere, and melting it for 6 hours to obtain a glass melt; cooling the glass melt to 1420°C-1460°C, pressing the glass melt into a mold at a molding temperature of 1280°C-1380°C, and obtaining a glass blank; placing the glass blank into an annealing furnace for annealing at a temperature of 550°C-650°C for 5 hours, and naturally cooling it to room temperature to obtain a basic glass.
[0110] (3) Preparation of microcrystalline glass: The base glass is placed in a crystallization furnace and subjected to a crystallization heat treatment by a step-by-step heating and cooling method: the temperature is raised to the crystallization temperature at a rate of 2°C / min to 5°C / min, and the crystallization temperature is 760°C; the temperature is kept at the crystallization temperature for 6 h, and then the temperature is lowered to room temperature at a rate of 0.5°C / min to 2°C / min to obtain microcrystalline glass.
[0111] (4) The crystal phase type and crystallinity of the microcrystalline glass prepared above were tested, and the results are shown in Table 1. At the same time, the thermal expansion coefficient (50°C~750°C) and softening temperature were measured using the NETZSCH DIL402 Expedis Classic thermal expansion instrument; the thermal shock temperature was tested according to the cold and hot shock resistance method specified in 6.2.3 of QB / T 4831-2015, the transmittance of the microcrystalline glass with a thickness of 4 mm was tested using the GBC Crintra2020 UV-visible spectrophotometer, the Mohs hardness grade was tested according to the Mohs hardness test method specified in 6.5.4 of JC / T872-2000, the ROR maximum force and ROR strength were tested using the Psett PT-307A, and the impact strength was tested and calculated using the Psett PT-706 drop ball impact tester; the performance test results of the microcrystalline glass prepared in Example 1 are shown in Table 1.
[0112] Embodiments 2 to 15
[0113] It is basically the same as Example 1, except that the component ratio of the microcrystalline glass, the melting temperature and time, and the crystallization temperature and time are different. Specifically, the microcrystalline glass components, process parameters and performance results of Examples 2 to 5 are shown in Table 1; the microcrystalline glass components, process parameters and performance results of Examples 6 to 10 are shown in Table 2; the microcrystalline glass components, process parameters and performance results of Examples 11 to 15 are shown in Table 3; the microcrystalline glass components, process parameters and performance results of Examples 16 to 20 are shown in Table 4; the microcrystalline glass components, process parameters and performance results of Comparative Examples 1 to 3 are shown in Table 5.
[0114] Table 1
[0115]
[0116] Table 2
[0117]
[0118] Table 3
[0119]
[0120] Table 4
[0121]
[0122] The softening temperature of the glass-ceramics prepared in Examples 1 to 20 of the present application is above 900°C, and the expansion coefficient is -2.6×10 -7 / ℃~5×10 -7 / ℃, the maximum ROR force reaches more than 2800N, the ROR strength reaches more than 73MPa, the impact strength reaches more than 0.72J, and the transmittance reaches more than 86%; it has the advantages of good heat resistance, low expansion coefficient, high mechanical strength, and transparent appearance.
[0123] In Example 16, the value of (MgO+ZnO) / Al2O3 is greater than 0.42, and the Mohs hardness of the obtained microcrystalline glass is only 6; in Example 18, the value of TiO2 / (ZrO2+P2O5) is greater than 0.97, and the impact strength of the obtained microcrystalline glass is only 0.725J; in Example 19, the value of (SiO2+Al2O3+Li2O+La2O3) / (TiO2+ZrO2+P2O5) is greater than 15.42, and the Mohs hardness of the obtained microcrystalline glass is only 6; in Example 20, the value of (MgO+ZnO+CaO+BaO) / (Na2O+Li2O) is 6.11, which is greater than 5.69, and the maximum ROR force of the obtained microcrystalline glass is only 2785N, the impact strength is only 0.713J and the thermal shock strength is less than 800℃.
[0124] Table 5
[0125]
[0126] In comparative example 1, the value of Na2O is greater than 1%, the thermal expansion coefficient of the prepared microcrystalline glass increases, the softening temperature decreases, and the Mohs hardness is only level 5; in comparative example 2, the value of Al2O3 is greater than 24.8%, the thermal expansion coefficient of the prepared microcrystalline glass increases, and the Mohs hardness is only level 6; in comparative example 3, the value of ZnO is greater than 5%, the thermal expansion coefficient of the prepared microcrystalline glass increases, the softening temperature decreases, the Mohs hardness decreases, and the impact strength is only 0.714J.
[0127] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0128] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A glass-ceramic, characterized in that: Calculated by mass percentage, it includes the following components: SiO2 54%~68%, Al2O3 15%~24.8%, Li2O 0.5%~4.5%, Na2O 0~1%, MgO 1%~5%, ZnO 1%~5%, CaO 0~1%, BaO 0~3%, TiO2 0.5%~4%, ZrO2 1%~5%, P2O5 0.5%~3% and La2O3 0.1%~1%.
2. The glass-ceramic according to claim 1, characterized in that: The sum of the mass percentages of TiO2, ZrO2 and P2O5 is a%, and satisfies 5.57≤a≤8.
73.
3. The glass-ceramic according to claim 1, characterized in that: The mass percentage of TiO2 is x%, the sum of the mass percentages of ZrO2 and P2O5 is y%, and 0.1≤x / y≤0.97 is satisfied.
4. The glass-ceramic according to claim 1, characterized in that: The sum of the mass percentages of SiO2, Al2O3, Li2O and La2O3 is m%, the sum of the mass percentages of TiO2, ZrO2 and P2O5 is n%, and 9.39≤m / n≤15.42 is satisfied.
5. The glass-ceramic according to claim 1, characterized in that: The sum of the mass percentages of MgO, ZnO, CaO and BaO is q%, the sum of the mass percentages of Na2O and Li2O is p%, and 1.52≤q / p≤5.69 is satisfied.
6. The glass-ceramic according to claim 1, characterized in that: The sum of the mass percentages of MgO and ZnO is b%, the mass percentage of Al2O3 is c%, and 0.21≤b / c≤0.42 is satisfied.
7. The glass-ceramics according to any one of claims 1 to 6, characterized in that: The microcrystalline glass satisfies at least one of the following conditions: (1) The glass-ceramics comprises the following components, measured by mass percentage: SiO2 56%-68%, Al2O3 15.5%-24.8%, Li2O 1.5%-4%, Na2O 0.5-1%, MgO 1.5%-3.5%, ZnO 1.5%-5%, CaO 0.3%-0.9%, BaO 0-3%, TiO2 1%-4%, ZrO2 1%-4%, P2O5 0.5%-2.4% and La2O3 0.1%-0.9%; (2) The main crystalline phase of the glass-ceramics includes one or more of quartz solid solution, spodumene and spinel; (3) The crystallinity of the glass-ceramics is 45% to 58%.
8. A method for preparing glass-ceramics, characterized in that: The steps include: Providing raw materials according to the components of the glass-ceramics according to any one of claims 1 to 7, and mixing the raw materials to prepare a mixture; The mixture is subjected to melting treatment, molding treatment, annealing treatment and crystallization treatment to obtain the microcrystalline glass.
9. The method for preparing glass-ceramics according to claim 8, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The melting treatment temperature is 1620°C to 1660°C and the time is 4h to 8h; (2) The temperature of the molding process is 1280°C to 1380°C; (3) The annealing treatment is performed at a temperature of 550°C to 650°C and for a time of 4h to 6h; (4) The crystallization treatment is performed at a temperature of 750°C to 900°C and for a time of 1.5h to 6h; (5) The crystallization step includes: heating to a crystallization temperature at a rate of 2°C / min to 5°C / min; (6) After the crystallization treatment, the following steps are included: cooling to room temperature at a rate of 0.5°C / min to 2°C / min.
10. A glass product, characterized in that: Including the microcrystalline glass as described in any one of claims 1 to 7 or the microcrystalline glass prepared by the preparation method of the microcrystalline glass as described in any one of claims 8 to 9.
Citation Information
Patent Citations
Microcrystalline glass, reinforced microcrystalline glass and preparation method thereof
CN111320392A
Aluminosilicate microcrystalline glass as well as preparation method and product thereof
CN111377614A
Low-expansion-coefficient transparent microcrystalline glass and preparation method thereof
CN116332517A
Glass ceramic and preparation method thereof
CN117756411A
Low-expansion microcrystalline glass and preparation method thereof
CN118206290A